De "Ilha da Magia" à "Ilha do Silício": patrimônio e narrativas em conflito no Centro Histórico de Florianópolis - Alexandre José Krause (Cadernos NAUI, 2023)
This article aims to identify spaces of order in dispute in the Historic District of Florianópolis and critically analyze the relationship between this material heritage and discourses of power; problematize the stances and recent interventions of public authorities that aim for a new identity for this District; recognize the articulation of a critical infrastructure and debate its influence on public opinion and political decisions in this central area.